2015
DOI: 10.1177/1524839914566851
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Physical Activity Outcome Improvements Resulting From a Church-Based Diet and Supervised Physical Activity Intervention for Rural, Southern, African American Adults

Abstract: We assessed the effects of a 6-month, church-based, diet and supervised physical activity intervention, conducted between 2011 and 2012, on improving diet quality and increasing physical activity of Southern, African American adults. Using a quasi-experimental design, eight self-selected, eligible churches were assigned to intervention or control. Assessments included dietary, physical activity, anthropometric, and clinical measures. Mixed model regression analysis and McNemar's test were used to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 19 publications
1
41
2
Order By: Relevance
“…Other church-based studies [20][21][22][23] with an all or predominantly African American study sample had higher retention (range of 73.0 to 84.0%) and older participants (mean age range of 47 to 60 years of age) compared to our phase 1 study while retention was comparable for phase 2. Additionally, the research reflects that most participants in similar studies were predominantly female and overweight/obese.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Other church-based studies [20][21][22][23] with an all or predominantly African American study sample had higher retention (range of 73.0 to 84.0%) and older participants (mean age range of 47 to 60 years of age) compared to our phase 1 study while retention was comparable for phase 2. Additionally, the research reflects that most participants in similar studies were predominantly female and overweight/obese.…”
Section: Discussioncontrasting
confidence: 58%
“…Additionally, the research reflects that most participants in similar studies were predominantly female and overweight/obese. Participants of three of the five [20][21][22][23][24] similar studies were at risk for diabetes [22] or were previously diagnosed with hypertension [23] or diabetes [24] as inclusion criteria. Overall, participants of similar studies [20][21][22][23][24] were older and had a greater prevalence of chronic disease compared to our baseline samples.…”
Section: Discussionmentioning
confidence: 99%
“…Church congregations often have resources such as active health ministries ( 17 ), stable membership over long periods of time ( 9 ), and members with deep social ties ( 16 ). Church-based health promotion interventions have resulted in increased physical activity ( 9 , 18 20 ), increased fruit and vegetable intake ( 19 , 21 24 ), and increases in cancer screening behaviors (e.g., mammography, colorectal cancer screening) ( 25 , 26 ). However, developing such fruitful partnerships with churches is a delicate process that requires investment in time and resources; development of trust; and thorough, systematic planning ( 9 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that the intervention was effective in improving diet quality and blood lipids, and increasing physical activity in this cohort. 12 Given the limitations of the literature, the objective of this secondary analysis was to evaluate the utility of several participant engagement indicators for predicting changes in dietary, physical activity, anthropometric, and clinical outcomes in Delta Body and Soul III. We hypothesized that participants with higher engagement in intervention components would have larger improvements in health outcomes as compared to control participants and intervention participants, both with lower levels of engagement.…”
mentioning
confidence: 99%